Plant protection consequences in Hungary of the withdrawal of systemic active substances from sugar beet seed treatment - Jócsák, Ildikó; Csima, Ferenc; Pál-Fám, Ferenc; Somfalvi-Tóth, Katalin; Keszthelyi, Sándor (Frontiers in Agronomy, 2024)
After decades of development, neonicotinoids were widely used in Hungarian sugar beet production and seeds included thiamethoxam treatment by 2019 increasing protection against early spring pests. In Hungary, neonicotides’ influence on bee health led to their removal of emergency authorization. In the absence of thiamethoxam in 2020, experience showed that multiple treatments were needed to protect beet from pests early spring pests. Repeated applications of mostly pyrethroids have proved suitable; however, in sugar beet, this has resulted in a multiple increase in environmental stress and honey bee mortality, as well as increased input values. The aim of this work is to explore the current state of production and collect new alternative options for applying effectively in Hungarian sugar beet production technology, against early spring pests.